Correlations between Berg balance scale and gait speed in individuals with stroke wearing ankle–foot orthoses – a pilot study. (2nd April 2016) - Kobayashi, Toshiki; Leung, Aaron K. L.; Akazawa, Yasushi; Hutchins, Stephen W.
Abstract: Purpose : The Berg balance scale (BBS) is commonly used to assess balancing ability in patients with stroke. The BBS may be a good candidate for clinical assessment prior to orthotic intervention, if it correlates well with outcome measures such as gait speed. The purpose of this study was to investigate the correlation between the BBS measured prior to walking with an ankle-foot orthosis (AFO) and specific temporal-spatial parameters of gait when walking with an AFO donned. Methods : Eight individuals with chronic stroke participated in this study. Balancing ability was assessed using the BBS, while temporal–spatial parameters of gait (gait speed, bilateral step length, stride length and step width) were measured using a three-dimensional motion analysis system. The correlations between the BBS and gait parameters were investigated using a non-parametric Kendall's Tau (τ) correlation analysis. Results : The BBS showed correlations with gait speed ( τ  = 0.64, p  < 0.05), the step length of the affected side ( τ  = 0.74, p  < 0.05), and the stride length ( τ  = 0.64, p  < 0.05). Conclusions : Assessment of the BBS prior to AFO prescription may potentially help clinicians to estimate the gait speed achievable following orthotic intervention in patients with stroke. Implications for Rehabilitation: Assessment of the BBS prior to AFO prescription may help orthotists to estimate the gait speed following an orthotic intervention in patients with stroke. Assessment of the BBS prior to AFO prescription may help orthotists to understand overall balance and postural control abilities in patients with stroke. A larger scale multifactorial analysis is warranted to confirm the results of this pilot study.